The effect of internet firms’ data analytics capability on their innovation speed and innovation quality: A dynamic capability perspective - HUA, Yeyu (Institutional Knowledge at Singapore Management University, 2024)
With the advent of big data era, data plays a pivotal role in sustainingfirms’ competitive advantages. Although a few studies have shown that data analytics capability contributes to firms’ innovative performance, these studies either focus on general innovative performance or specific types of innovation, such as incremental innovation, radical innovation, and supply chaininnovation. In this thesis, I enrich this stream of literature by conducting twostudies to further examine the relationship between data analytics capabilityand innovation speed as well as innovation quality. This thesis consists of twostudies. Study 1 is a survey study, in which I investigate the relationshipbetween data analytics capability and innovation speed as well as the boundary conditions for this relationship. Study 2 is also a survey study, inwhich I explore the relationship between data analytics capability andinnovation quality as well as the boundary conditions underlying this relationship. Based on my analyses of a sample of 459 Internet firms, I findthat data analytics capability is positively associated with both the speed andquality of innovation. Overall, the two studies in my thesis depict anoverarching theoretical framework that links data analytics capability toinnovation speed and innovation quality as well as the boundary conditions. This framework offers a clear picture for researchers and practitioners tounderstands how to leverage data analytics to drive innovation speed andinnovation quality in the digital era.